Smart "on-off-on" fluorescent switches for drug visual loading and responsive delivery. (February 2020) - Gong, Peiwei; Zhang, Lei; Peng, Jingyi; Li, Shuohan; Chen, Junfeng; Liu, Xicheng; Peng, Hongwei; Liu, Zhe; You, Jinmao
Abstract: The unsatisfactory therapeutic effects and limitations of chemotherapy are urging people to find more effective therapy methods, and drug delivery systems have been attracting increasing research interests. However, most of these studies mainly focused on the therapeutic effects, while little attention was paid to explore new drug loading patterns and improve the efficiency. Herein, a pair of smart "on-off-on" fluorescent switches based on a novel double fluorescence resonance energy transfer (FRET) system was established to realize facilely visual drug loading and responsive delivery. To build this nanosystem, highly luminescent carbon quantum dots (CQDs) were first prepared and further loaded by anticancer drugs of doxorubicin (DOX). The π-π and hydrogen-bonding interactions between them readily formed the first FRET system, which allowed to facilely monitor the drug loading process by detecting the solution color changes with naked eyes. Then, manganese dioxide (MnO2 ) with high surface area, further modified by polydopamine and folic acid was synthesized and served as the other FRET receptor for CQDs and DOX, facilitating monitor of full drug absorption and loading by total fluorescence quenching. Moreover, when the double-FRET nanosystem was endocytosed into cancer cells, MnO2 was responsively degraded into Mn 2+ under intracellular glutathione and acid conditions, which resulted into sustained drug release and gradual fluorescence recovery. More importantly, the constructed nano-system also exhibited selectively drug delivery and showed much finer therapeutic effects than single chemotherapy, holding great potential in future cancer therapy. Graphical abstract: A pair of smart "on-off-on" fluorescent switches based on a novel double fluorescence resonance energy transfer system was established to realize facilely visual drug loading and responsive delivery. Image 1 Highlights: Well surface-modified MnO2 with high surface area and brightly fluorescent carbon quantum dots were effectively synthesized. A pair switches based on FRET mechanism was constructed, and allowed visual monitor of drug loading with naked eyes for the first time. The nanosystem enabled targeted delivery, responsive release and biodegradation triggered by glutathione and H + in tumor microenvironment.